PENGGUNAAN KEEFEKTIVITASAN MEDIA MOBILE LEARNING DALAM MENINGKATKAN PELAFALAN HANYU PINYIN BAHASA MANDARIN - Hermawan, Budi; Leonardo, Ong Peter (Universitas Negeri Surabaya, 2017)
Globalisation Era will be faced Indonesia in 21st century. Chinese Language’s role is really needed in many aspect and sectors. Human resources who expert in foreign language are really needed as a bridge to cooperate between Indonesian and other countries. At this time the quantity student of Chinese Language in Indonesia have increased very fast. Many students with many ways have joined to expert Chinese Language in formal education or nonformal education. They all of them have tried to expert this foreign language. But there is a problem for Indonesian students to learn Chinese Language. The problem is a quite diffrent pronounciation with Indonesia Language before. So, at the last time so many students have given up to decide dismiss from the particular Chinese lesson. At this century, the technology also increase very fast. It’s related with many application to the smart phone. In the beginning of 2000th year, it has increased android system and ios which so many person have these system with many diffrent type. From the qualitative research method that we had done before. It’s known that the student of Chinese Language in using mobile learning can support to learn pronounciation, expecially for the consonant.